Postoperative pain relief in children after subumbilical surgeries-a comparison between caudal bupivacaine and bupivacaine-clonidine - Bhowmick, DK; Akhtaruzzaman, KM; Ahmed, N; Islam, MS; Hossain, MM; Islam, MM (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):93-97 The abstract of this article is available on the PubMed website